Joseph Conrad’s Criticism of Imperialism and Colonialism Through Literature - Contreras, Efrain (The Toro Historical Review, 2024)
This paper looks into the early criticism of imperialism and colonialism through literature. Mainly through Joseph Conrad’s novella Heart of Darkness. The paper examines how Heart of Darkness paints the reality created by King Leopold II of Belgium in the Congo. Conrad does this through his characters, which not only criticize King Leopold, but other colonial powers of the time as well. The book is also used by Conrad to share his personal experience in the Congo and to spread awareness of the hypocrisy of nationalism and imperialism. This paper highlights the influence of the book and its contributions to the global agenda to end King Leopold's rule in the Congo.